Self-adjuvanted hyaluronate – antigenic peptide conjugate for transdermal treatment of muscular dystrophy. (March 2016) - Kong, Won Ho; Sung, Dong Kyung; Kim, Hyemin; Yang, Jeong-A; Ieronimakis, Nicholas; Kim, Ki Su; Lee, Jeehun; Kim, Deok-Ho; Yun, Seok Hyun; Hahn, Sei Kwang
Abstract: Duchenne's muscular dystrophy (DMD) is a neuromuscular disorder accompanied with muscle weakness and wasting. Since myostatin was reported to be a key regulator of muscle wasting, myostatin inhibitors have been investigated as therapeutic candidates for the treatment of muscular diseases. Here, we report an antigenic peptide of myostatin fragment (MstnF) conjugated to hyaluronate (HA) with a low molecular weight (MW, 17 kDa) for transdermal immunotherapy of DMD. Facilitating the transdermal delivery, the low MW HA showed a boosting effect on the immunization of MstnF possibly by engaging both toll-like receptors and cluster of differentiation 44 (CD44). In vivo two-photon microscopy clearly visualized the effective transdermal penetration of HA-MstnF conjugates into deep intact skin layers. The transdermal immunization of mdx mice significantly increased antibody titers against myostatin. Furthermore, the mdx mice immunized with HA-MstnF conjugates resulted in statistically significant improvement in the biochemical and pathological status of skeletal musculature as well as functional behaviors.